The Influence of The Quality, Health, Safety And Environment (QHSE) Department Strategy On Reducing Workplace Accident Rates Through Occupational Health and Safety Discipline at PT. Bumi Siak Pusako - Muhammad Andri; Raden Lestari Garnasih; Any Widayatsari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of the Quality, Health, Safety and Environment (QHSE) department strategy on reducing workplace accident rates through occupational health and safety (OHS) discipline at PT Bumi Siak Pusako. This research employed a quantitative method. The population in this study consisted of 414 employees and work partners at PT Bumi Siak Pusako in the Zamrud area. The sample consisted of 203 employees and operational work partners. The findings of this study indicate that the QHSE strategy has a positive and significant effect on workplace accident rates. In addition, the QHSE strategy also has a positive and significant effect on OHS discipline. Furthermore, OHS discipline has been proven to have a positive and significant effect on workplace accident rates. The QHSE strategy also has an indirect effect on workplace accident rates through OHS discipline. Moreover, the QHSE Department of PT Bumi Siak Pusako effectively strengthens OHS discipline through the implementation of structured systems, supervision, and increased employee awareness, thereby reducing the risk of workplace accidents through preventive and corrective approaches.